Biology and clinical outcomes of early primary breast cancer in older women: a study based on core needle biopsy - Albanghali, Mohammad (2016)
Background: Older women with breast cancer (BC) appear to have more favourable biology compared to their younger counterparts. However, most studies involving older women with BC used surgical excisions (SE) to profile the tumour biology. Given that (i) older women are more likely to have oestrogen receptor (ER) positive BC and (ii) treatment decisions are complex which often take into account patients’ choice and/or age associated comorbidities, there is expected bias towards having more ER-positive diseases in the group of patients receiving non-operative treatments, notably primary endocrine therapy (PET), and proportionally slightly more ER-negative diseases in the surgical group. Hence, simply characterising the tumour biology according to SE might result in significant bias.